Assessment of a primal-dual interior point method using a three-D filter line search strategy - Costa, M. Fernanda P. (2010)
In this paper, we analyze a possible way to implement a filter line search approach based on three measures in a primal-dual interior point method for nonlinear programming. Two measures arise directly from the first order optimality conditions of the problem and the other is the barrier function. We solve a well-known set of small and medium-scale optimization problems and the results show that such an approach is effective in reaching the solutions.